The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/j.otohns.2003.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Laser Salvage Surgery after Radiotherapy Failure in T1 and T2 Glottic Carcinoma

Abstract: The present series indicates that selected recurrences after primary RT for T1 and T2 glottic carcinoma are eligible for endoscopic salvage surgery with oncologic results comparable to those with open neck procedures but with a lower complication rate and a favorable functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…[1][2][3] Local recurrence rate after radiation therapy (RT) ranges from 5% to 13% for T1 and from 25% to 30% for T2 laryngeal cancer. 4,5 Surgical management of recurrences after RT failure encompasses endoscopic laser excision, [6][7][8] partial laryngectomies through an open-neck approach, 4,[9][10][11][12][13] and total laryngectomy, which still remains the most widely used procedure in such a scenario.…”
mentioning
confidence: 99%
“…[1][2][3] Local recurrence rate after radiation therapy (RT) ranges from 5% to 13% for T1 and from 25% to 30% for T2 laryngeal cancer. 4,5 Surgical management of recurrences after RT failure encompasses endoscopic laser excision, [6][7][8] partial laryngectomies through an open-neck approach, 4,[9][10][11][12][13] and total laryngectomy, which still remains the most widely used procedure in such a scenario.…”
mentioning
confidence: 99%
“…The series of Puxeddu et al [15] is a two-center retrospective case series, with results of one included center updated in a later publication by Piazza et al [16], which, in turn, was updated by Del Bon et al [17]. Most authors reported on series of rT1 to rT2 glottic cancer, while some authors also included more advanced glottic cases (rT3 or even rT4) [11••, 1821] or supraglottic recurrences [14, 18, 2022].…”
Section: Resultsmentioning
confidence: 99%
“…Most authors noticed higher rates of the development of a second recurrence following salvage TLM in patients with AC involvement when compared to patients with the AC free of tumor: second recurrence rates of 50 versus 11% [18], 71 versus 48% [23], 67 versus 8% [15], and 55 versus 29% [24], respectively, were reported. On univariate analysis, Han et al identified AC involvement as a negative prognostic factor for 3-and 5-year local control rates (51.9 versus 85.7% and 0 versus 64.2%, p  = 0.09) [24].…”
Section: Resultsmentioning
confidence: 99%
“…1,4 This subsequently makes the cricothyroid membrane and anterior commissure ligament more susceptible to direct extension of tumor.…”
Section: Anatomic Point #1mentioning
confidence: 99%
“…The mainstay surgical treatment option for most early lesions is typically via a transoral approach, with shorter hospitalizations, lower morbidity, and improved functional results. 1 However, this review will focus on transcervical approaches and discuss their seminal anatomic principles. Open approaches can be considered in situations where exposure is inadequate for transoral resection, or the transoral technique is not in the purview of the institution, as well as for salvage surgery after radiation failure.…”
mentioning
confidence: 99%